A comparison of the dechlorination mechanisms and Ni release styles of chloroalkane and chloroalkene removal using nickel/iron nanoparticles. Issue 16 (17th August 2016) - Zhang, Wei; Jia, Nan; Han, Xiaolin; Qiu, Zhaofu; Lv, Shuguang; Lin, Kuangfei; Ying, Weichi
ABSTRACT: In this study, we compared the removal kinetics and Ni release styles of 1, 1, 1-trichloroethane (1, 1, 1-TCA), trichloroethylene (TCE), and tetrachloroethene (PCE) that result from the use of Ni/Fe nanoparticles in water. Compared to TCE and PCE, 1, 1, 1-TCA was more readily removed, and the concentration profiles of the three chlorinated aliphatic hydrocarbons (CAHs) during the reduction processes fit pseudo-first-order reaction rate models well. The surface area-normalized rate constants show that the 11% Ni Ni/Fe nanoparticles, which has the largest Brunauer–Emmett–Teller surface area, has the highest capacity for 1, 1, 1-TCA removal per unit surface area and that the 6% Ni sample was the best for removing TCE and PCE. The observed by-products suggested that hydrogenolysis was responsible for the dechlorination of CAHs in the presence of Ni/Fe nanoparticles. More Ni2+ was released during the degradation of 1, 1, 1-TCA than that of TCE and PCE because Ni will reduce the CAHs directly as a zerovalent metal does when hydrogen atoms in the Ni lattice are not sufficient due to the rapid incomplete dechlorination of 1, 1, 1-TCA. The different modes of adsorption of chloroalkane and chloroalkene onto the surfaces of Ni/Fe particles might play an important role in their dechlorination process. GRAPHICAL ABSTRACT: